2009
DOI: 10.1152/ajpcell.00144.2009
|View full text |Cite
|
Sign up to set email alerts
|

Closed-state inactivation in Kv4.3 isoforms is differentially modulated by protein kinase C

Abstract: Kv4.3, with its complex open- and closed-state inactivation (CSI) characteristics, is a primary contributor to early cardiac repolarization. The two alternatively spliced forms, Kv4.3-short (Kv4.3-S) and Kv4.3-long (Kv4.3-L), differ by the presence of a 19-amino acid insert downstream from the sixth transmembrane segment. The isoforms are similar kinetically; however, the longer form has a unique PKC phosphorylation site. To test the possibility that inactivation is differentially regulated by phosphorylation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Accordingly, several isoforms with different functional phenotypes exist (22,200,223,327,402,404,460,469,499). The alternative splicing increases the redundancy of the channels, but also helps to diversify the function of the multimeric proteins.…”
Section: Posttranscriptional Mechanismsmentioning
confidence: 99%
“…Accordingly, several isoforms with different functional phenotypes exist (22,200,223,327,402,404,460,469,499). The alternative splicing increases the redundancy of the channels, but also helps to diversify the function of the multimeric proteins.…”
Section: Posttranscriptional Mechanismsmentioning
confidence: 99%
“…We further propose that compared to the muscle isoform, RBFOX240 stimulates the higher-order assembly of LASR complex 46,47 , which boosts its splicing activity, resulting in altered isoform expression of proteins that can disrupt the normal cardiac rhythm and function. Indeed, we demonstrated that RBFOX240 promotes the generation of pathogenic splice variants of voltage-gated sodium and potassium channels that are known to exhibit slower conduction velocity and increased susceptibility to arrhythmias 52,54,68,69 . Our MD simulations showed that a RBFOX240-mediated splicing switch in Nav1.5 transcript changes the amino acid composition of the voltage sensing element within domain I that promotes persistent lipid-interactions and stabilizes the 310-helical conformation of S4 helix, which reduces the energy barrier and allows for rapid deactivation of the channel.…”
Section: Discussionmentioning
confidence: 98%
“…Amongst these amino acids is a conserved threonine residue, which is phosphorylated by protein kinase C to facilitate regulation of transient outward current Ito 68 . The KV4.3 isoform lacking the 57-nt exon has been shown to promote faster inactivation of the channel, which slows down the ion flux and lengthens the duration of action potential-particularly affecting the early recovery and plateau phases of repolarization 69 .…”
Section: Structure-function Analysis Of Dm1-associated Alternatively mentioning
confidence: 99%
“…The two known human Kv4.3 splice variants, Kv4.3L and Kv4.3S, were previously thought to function similarly at baseline, but differently with respect to their regulation by PKC, because of PKC phosphorylation of T504 in the C-terminal 19-residues that are found only in Kv4.3L (Po et al, 2001 ; Xie et al, 2009 ). Yet, the author recently found that co-expression with KChIP2b or KCNEs co-expression reveals important functional differences between Kv4.3L and Kv4.3S, namely that KChIP2 favorably augments Kv4.3S vs. Kv4.3L activity (four- vs. two-fold), and that Kv4.3S-KChIP2b channels are faster inactivating, and exhibit negative-shifted steady-state inactivation, compared to Kv4.3L-KChIP2b (Abbott, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C (PKC) phosphorylation of T504 within this consensus site mediates inhibition of human Kv4.3L, facilitating physiologically important α-adrenergic regulation of cardiac I to (Po et al, 2001 ). In contrast, others found that for rat Kv4.3, PKC stimulation (10 nM PMA for 30 min) inhibited both long and short forms, T504A-Kv4.3L-indepedently, with the only isoform-dependent difference being differentially altered closed-state inactivation (decreasing it in Kv4.3S, increasing it in Kv4.3L; Xie et al, 2009 ).…”
Section: Introductionmentioning
confidence: 93%